Modeling And Control Of Excitation And Governor Based On Particle Swarm Optimization For Micro Hydro Power Plant - Muhamad Haddin; Soebagio Soebagio; Adi Soeprijanto; Mauridhi Hery Purnomo (Universitas Ahmad Dahlan, 2013)
This paper presents the modeling and control of the excitation system via the automatic voltage regulator (AVR) and governor system through the automatic generation control (AGC) or frequency load control (FLC) to improve stability on a micro hydro power plant (MHPP). Three main parts of the generation system are synchronous generator, AVR-excitation, AGC modelled linearly. Generator is modelled by a single machine connected to infinite bus (SMIB) which is equipped by AVR and excitation linear model. Excitation control system made by optimizing the gain of the AVR (KA) and the governor with the gain of the AGC (Ki). Optimization is done using the method improved particle swarm optimization (IPSO). The main purpose of setting the gain of the AVR-AGC is to stabilize the oscillation frequency of the MHPP which is connected to an infinite bus. Simulations are conducted by inputting step function with 5% load fluctuations as a representation of dynamic load. The simulation results show that the proposed method effectively raises the level of electromechanical damping oscillations the SMIB by generating the comprehensive damping index (CDI) is minimum.